2018
DOI: 10.21053/ceo.2017.01753
|View full text |Cite
|
Sign up to set email alerts
|

Swing-Door Overlay Tympanoplasty: Surgical Technique and Outcomes

Abstract: Objectives The classical overlay tympanoplasty is technically difficult with some disadvantages and thus less popular. However, it is particularly useful for large, anterior perforations. In this study, we describe the technique of a modified overlay graft in the tympanoplasty coined as the swing-door overlay tympanoplasty and report its outcomes.Methods Retrospective review of patients undergoing the swing-door overlay tympanoplasty at a tertiary referral center between 2003 and 2016 was performed. Patient wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…However, the reportedstudy had a limitation in its rationale on theeffect of MEPM as the conditions were not controlled. Previous clinical studies without gelfoam during overlay tympanoplasty or ossiculoplasty demonstrated excellentsurgical results, which guided us to perform a more scientific and clinical study to demonstrate the effect of MEPM 3,17 . Our study is the first prospective randomized case-control study to investigatethe effects of middle ear packing using AGS in terms of surgical results and healing processes in humans.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…However, the reportedstudy had a limitation in its rationale on theeffect of MEPM as the conditions were not controlled. Previous clinical studies without gelfoam during overlay tympanoplasty or ossiculoplasty demonstrated excellentsurgical results, which guided us to perform a more scientific and clinical study to demonstrate the effect of MEPM 3,17 . Our study is the first prospective randomized case-control study to investigatethe effects of middle ear packing using AGS in terms of surgical results and healing processes in humans.…”
Section: Discussionmentioning
confidence: 96%
“…All patients underwent swing-door overlay tympanoplasty 3 . Under general anaesthesia, the temporalis muscle facia harvested as usual.…”
Section: Surgical Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Different tympanoplasty techniques have been shown successful outcomes. [7][8][9] Underlay tympanoplasty involves placing the graft under the remnant tympanic membrane and manubrium mallei. 10 In a meta-analysis, Tan et al reported that similar outcomes were observed between the underlay and the overlay techniques, but graft lateralization was observed mostly after the overlay technique.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the graft success rate is high (more than 90%). The most major disadvantages are the blunting of the anterior portion of TM, iatrogenic cholesteatoma, and lateralization of the graft; however, this procedure needs more experience of the surgeon, and the recovery time is slower 11,12 …”
Section: Introductionmentioning
confidence: 99%